Effect of Graphene Nanoplatelets on Tribological Properties of Bacterial Cellulose/Polyolester Oil Bio-Lubricant - Fuadi, Zahrul; Rahmadiawan, Dieter; Kurniawan, Rudi; Mulana, Farid; Abral, Hairul; Nasruddin, Nasruddin; Khalid, Mohammad (Frontiers in Mechanical Engineering, 2022)
The demand for bio-degradable lubricants is continuously increasing due to environmental concerns. One of the methods to achieve the bio-degradability property of lubricants is by using nanoparticles from bio-resources as additives in bio-degradable oils. Among the nanomaterials are nanofibers, cellulose, and graphene nanoplatelets. They can be mixed in Polyolester (POE) oil to produce lubricants for tribological applications. In a previous study, it has been confirmed that friction and wear of the tribo-pair reduced from 5% to 10% by mixing various volume percentages of bacterial cellulose (BC) into PEO as the base lubricant. The tribological performance BC containing POE base lubricant can further be enhanced by incorporating graphene nanoplatelets. This study shows that the specific wear rate of the material decreased by 20% by adding graphene nanoplatelets in BC containing POE oil. The friction and wear improvement can be related to the formation of tribofilm on the contact interface. EDS analysis indicates that oxygen played an important role in the friction and wear performance of the POE oil-based lubricant with BC and graphene additives. The tribofilm shows significant traces of oxygen elements. The presence of graphene nanoplatelets in POE oil removed the oxygen-rich layer but could not reduce the wear rate. However, incorporating both graphene and BC in POE oil significantly improved friction and wear, although the oxygen element was still traceable on the contact interface.